Occupational Variation in Durgapur City, West Bengal - Singh, Alka; Sharma, V.N. (National Geographical Journal of India, 2022)
The occupational structure of the country implies involvement of its population in economic activities of various sectors. These are divided into a) Primary activity (agriculture, fishing, mining, quarrying), b) Secondary activity (household and manufacturing) and c) Tertiary activity (transport, trade, and other services).This paper presents the changing pattern of occupational structure in Durgapur city (West Bengal) from 1981 to 2011.The development of Durgapur city was itself a part of regional resource development plan, that comes with big bang of a new era of industrialization after independence. Since primary activity has been the base of economy for a long time along with development of secondary activities but, in recent times, it is shifting towards tertiary activities. There were 26.37% main worker, 0.33% marginal worker, and 73% non-worker in 1981 whereas in 2011 main worker reached to 26.92% and with 8% light increase in marginal worker reached to 8.21% and with decrease non-worker reached to 64.87%. There was change in percentage of occupational types during 1981 to 2011. There were 0.34% cultivator, 1.01% agricultural labour, 0.50% household and manufacturing workers and 24.79% workers in other services in 1981 which were recorded in 2011 as 0.39% cultivator, 0.82% agricultural labour, 0.80% household and manufacturing workers and 32.47% workers in other services. The analysis draws our attention towards change in occupational structure oriented to tertiary activities which is not a good sign for future development because primary and secondary activities are the base of economy and tertiary activity is only the supportive one.